The standard model and beyond : proceedings of the 2nd International Summer School in High Energy Physics, Muğla, 25-30 September 2006 - Aliev, T. (Springer, 2017)
Front Matter; Introduction to Chiral Perturbation Theory; Introduction to Higgs Sector: Theory and Phenomenology; Heavy Flavor and B Physics; CP Violation: Experimental Results in B Decays; Worldline Formalism and It's Application to AdS/CFT Correspondence; Course on Grand Unification; Neutrino Physics and Astrophysics: Highlights; Back Matter.